Exploration of junior high school students perseverance in mathematical reasoning on data presentation material - Novita Sari; Rohati; Ade Kumalasari (LINEAR: Journal of Mathematics Education, 2025)
This qualitative study explores Perseverance in Mathematical Reasoning (PiMR) in a junior high school student while solving a Data Presentation problem. A qualitative approach was chosen to gain an in-depth and contextual understanding of the subject's reasoning process and behaviors. The background for this study is the low level of mathematical reasoning perseverance among Indonesian students, which is a crucial ability. This study used a PISA-model written test and an interview with one seventh-grade subject. Data were analyzed using the Miles and Huberman model through data reduction, data display, and conclusion drawing. In general, the subject successfully demonstrated some indicators of PiMR, such as exploring solutions and attempting to correct answers. However, the main finding reveals the subject's inability to adjust strategies when facing an impasse, which resulted in the final answer remaining incorrect. The implication of this research emphasizes the need for targeted educational support to develop mathematical reasoning perseverance in students that is not only persistent but also more adaptive and sustainable.